Programming Tools PT 2 (MATLAB):Tutorial for Second-Year Math Students - LEULMI , Assma (Setif 1 University Ferhat Abbas . Faculty of Sciences, 2025)
This booklet serves as a support for the Programming Tools (Matlab) course in the second year of the Bachelor's degree in Mathematics and Technology (ST), Bachelor's degree in Material Sciences (SM) (Physics and Chemistry), and engineering training programs (ST, ME, etc.). The objective of this course is to familiarize students with a set of tools (algorithms) aimed at efficiently solving various problems. The chapters are illustrated with application examples, and a series of exercises is provided at the end of each chapter. It covers: Introduction to the Matlab environment, Vectors and matrices, Introduction to programming with Matlab, and Graphs and data visualization in Matlab.
Keywords: Matlab; Vectors; Matrices; Programming with Matlab; Graphs; Data visualization in Matlab